Transformasi Sistem Pendidikan Full Day School Di Era Globalisasi Di SD IT Bungaraya - Masfufah, Siti; Indah Permata , Dian (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2023)
In this era of globalization, the world of education must carry out a reconstruction of thinking, towards thinking that is more transformative and has a global perspective. In this modern era, information can be obtained from advances in information technology, such as the internet. So Freire's view which states that there is suppression of creativity and the development of student potential becomes true, if the application of traditional learning methods such as lectures is no longer appropriate with the current educational paradigm. Educational institutions are a form of social and cultural structure in a society. Changes in elements in culture will bring changes to a norm, and from these changes in norms will also bring changes to social institutions. Thus cultural change can change social organization. If an educational institution such as a school cannot keep up with social change, then it will lose its function and it is likely that it will be abandoned by society. Therefore, through educational practice, students are invited to understand how history or cultural experience can be transformed in the era of life they will experience and prepare them to face the challenges and demands that lie within. As a strategic step, researchers will discuss how the world of education must carry out a reconstruction of thinking towards thinking that is more transformative and has a global outlook, namely a thinking that is able to read the real conditions of society. In this study the method used was a qualitative method with a descriptive study type of research and data collection techniques were carried out by direct observation, interviews (in-depth interviews), and document studies